Case Report: Active tuberculosis infection in CAR T-cell recipients post CAR T-cell therapy: a retrospective case series - Zhang, Peiling; Huang, Liang; Zheng, Miao; Zhang, Chao; Wan, Dongyi; Wei, Jia; Cao, Yang (Frontiers in Cellular and Infection Microbiology, 2023)
High response rates in B-cell malignancies have been achieved with chimeric antigen receptor (CAR) T-cell therapy. Emerging reports indicate a risk of active tuberculosis (TB) with novel immunotherapy for tumors. However, studies of TB in patients post CAR T-cell therapy are limited. In this case series study, we describe five patients with active TB post CD19/CD22 target CAR T-cell therapy alone or following autologous stem cell transplantation (ASCT). One of the patients developed active TB within the first 30 days post CAR T-cell therapy, and fever was the dominant presenting symptom; extrapulmonary manifestations of active TB were common in the other four patients and manifested after the first 30 days of CAR T-cell therapy. Four of the five patients improved with anti-TB treatment, but one patient with isoniazid resistance died of central nervous system TB infection. Our study provides the first series report of active TB following CD19/CD22 target CAR T-cell therapy.